Association of elective and emergency cesarean delivery with early childhood overweight at 12 months of age - Cai, Meijin (2020)
Importance: Global cesarean delivery (CD) rates have more than doubled over the past 2 decades, with an increasing contribution from elective CDs. Cesarean delivery has been linked to early childhood overweight and obesity, but limited studies have examined elective and emergency CDs separately. Objective: To investigate whether elective or emergency CD was associated with risk of early childhood overweight. Design, Setting, and Participants: Data were drawn from the Growing Up in Singapore Toward Healthy Outcomes (GUSTO) study, an ongoing prospective mother-child birth cohort study. Participants were pregnant women aged 18 years or older with homogeneous parental ethnic background in their first trimester recruited between June 2009 and September 2010 (n = 1237) at 2 major public hospitals in Singapore. Those with type 1 diabetes or undergoing chemotherapy or psychotropic drug treatment were excluded. Data analysis commenced in October 2017. Exposures: Delivery mode obtained from clinical records. Elective and emergency CD examined separately against vaginal delivery as reference. Main Outcomes and Measures: Body mass index–for–age z scores at age 12 months calculated based on 2006 World Health Organization Child Growth Standards from infant weight and recumbent crown-heel length measurements taken between December 2010 and April 2012. High body mass index status at risk of overweight was defined as a z score of more than 1 SD and less than or equal to 2 SDs. Overweight was defined as a z score of more than 2 SDs. Results: Among 727 infants analyzed (51.2% [372] male), 30.5% (222) were born via CD, of which 33.3% (74) were elective. Prevalence of at risk of overweight and overweight at age 12 months was 12.2% (89) and 2.3% (17), respectively. Elective CD was significantly associated with at risk of overweight or overweight at age 12 months after adjusting for maternal ethnicity, age, education, parity, body mass index, antenatal smoking, hypertensive disorders of pregnancy, gestational diabetes, and sex-adjusted birth weight–for–gestational age (odds ratio, 2.05; 95% CI, 1.08-3.90; P = .03). The association persisted after further adjustment for intrapartum antibiotics and first 6 months infant feeding, 2 potential mediators of early childhood overweight and obesity (odds ratio, 2.02; 95% CI, 1.05-3.89; P = .04). No significant associations were found for emergency CD. Analysis with multiple imputation for missing covariates yielded similar results. Conclusions and Relevance: Choice of delivery mode may influence risk of early childhood overweight. Clinicians are encouraged to discuss potential long-term implications of elective CD on child metabolic outcomes with patients who intend to have children.